Differential expression of interferon-lambda receptor 1 splice variants determines the magnitude of the antiviral response induced by interferon-lambda 3 in human immune cells. - Deanna M Santer; Gillian E S Minty; Dominic P Golec; Julia Lu; Julia May; Afshin Namdar; Juhi Shah; Shokrollah Elahi; David Proud; Michael Joyce; D Lorne Tyrrell; Michael Houghton (PLoS Pathogens, 2020)
Type III interferons (IFN-lambdas(λ)) are important cytokines that inhibit viruses and modulate immune responses by acting through a unique IFN-λR1/IL-10RB heterodimeric receptor. Until now, the primary antiviral function of IFN-λs has been proposed to be at anatomical barrier sites. Here, we examine the regulation of IFN-λR1 expression and measure the downstream effects of IFN-λ3 stimulation in primary human blood immune cells, compared with lung or liver epithelial cells. IFN-λ3 directly bound and upregulated IFN-stimulated gene (ISG) expression in freshly purified human B cells and CD8+ T cells, but not monocytes, neutrophils, natural killer cells, and CD4+ T cells. Despite similar IFNLR1 transcript levels in B cells and lung epithelial cells, lung epithelial cells bound more IFN-λ3, which resulted in a 50-fold greater ISG induction when compared to B cells. The reduced response of B cells could be explained by higher expression of the soluble variant of IFN-λR1 (sIFN-λR1), which significantly reduced ISG induction when added with IFN-λ3 to peripheral blood mononuclear cells or liver epithelial cells. T-cell receptor stimulation potently, and specifically, upregulated membrane-bound IFNLR1 expression in CD4+ T cells, leading to greater antiviral gene induction, and inhibition of human immunodeficiency virus type 1 infection. Collectively, our data demonstrate IFN-λ3 directly interacts with the human adaptive immune system, unlike what has been previously shown in published mouse models, and that type III IFNs could be potentially utilized to suppress both mucosal and blood-borne viral infections.